Epoxidation of cyclic enones with hydrogen peroxide catalysed by alkylcarboxylate-intercalated Ni–Zn mixed basic salts. Issue 1 (10th October 2014) - Hara, Takayoshi; Kurihara, Jun; Ichikuni, Nobuyuki; Shimazu, Shogo
Abstract : The interlayer spacing of layered Ni–Zn mixed basic salts (NiZn) can be precisely controlled by the intercalation of various long alkyl chain carboxylate anions into the NiZn interlayer. Abstract : The interlayer spacing of layered Ni–Zn mixed basic salts (NiZn) can be precisely controlled by the intercalation of various long alkyl chain carboxylate anions into the NiZn interlayer. The butyrate-exchanged NiZn (C3 H7 COO − /NiZn) catalyst effectively promotes the epoxidation of various cyclic enones with aqueous hydrogen peroxide in remarkably high yields. The C3 H7 COO − /NiZn-catalysed epoxidation of 2-cyclohexen-1-one with an equimolar amount of H2 O2 proceeds in a highly efficient manner, with 97% efficiency of H2 O2 utilization. This C3 H7 COO − /NiZn catalyst can be reused without any loss of its catalytic activity and selectivity.